HOW TO PREPARE FOR AN AVIAN INFLUENZA H5N1 PANDEMIC OUTBREAK:LESSONS LEARNED FROM THE INFLUENZA H1N1 PANDEMIC OF 1918 - Bhatia, Sudhir (Sanamed, 2024)
In this paper, we highlight the significant challenges encountered during the influenza H1N1 pandemic of 1918. These lessons are being utilized to prepare for potential avian influenza H5N1 pandemic outbreaks, as this virus will impact both humans and food-serving animals. Preparation for this threat is crucial because H5N1 infections are already affecting the United States and many other countries.
Keywords: Avian influenza H5N1; Bird flu; Pandemic outbreak; Influenza A; Food security